1978
DOI: 10.1063/1.325219
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic guidance of drug-carrying microspheres

Abstract: Physical laws underlying the intravascular magnetic guidance of a novel drug carrier are discussed. The drug carrier is a magnetically responsive drug-bearing microsphere measuring approximately 1 μm in diameter. The microspheres consist of an albumin matrix in which a prototype drug (adriamycin HCl) and ultrafine Fe3O4 particles are entrapped. An in vitro analog of the human circulatory system is used to test both bipolar and unipolar magnetic arrangements which can retain microspheres flowing in aqueous susp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
139
0
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(145 citation statements)
references
References 8 publications
0
139
0
6
Order By: Relevance
“…En concreto, proponemos el empleo de sistemas magnéticos de liberación. La idea de emplear partículas magnéticas como método de conducir el fármaco y favorecer su acumulación nació en los años 70 (Widder et al, 1979;Senyei et al, 1978). Sin embargo, sólo recientemente se ha profundizado en las aplicaciónes biomédicas de las nanopartículas magnéticas, en aspectos tales como imagen por resonancia magnética (Schlorf et al, 2011), hipertermia, o liberación de fármacos y genes (Gupta et al, 2007;Viota et al, 2011).…”
Section: Introducción Objetivosunclassified
See 2 more Smart Citations
“…En concreto, proponemos el empleo de sistemas magnéticos de liberación. La idea de emplear partículas magnéticas como método de conducir el fármaco y favorecer su acumulación nació en los años 70 (Widder et al, 1979;Senyei et al, 1978). Sin embargo, sólo recientemente se ha profundizado en las aplicaciónes biomédicas de las nanopartículas magnéticas, en aspectos tales como imagen por resonancia magnética (Schlorf et al, 2011), hipertermia, o liberación de fármacos y genes (Gupta et al, 2007;Viota et al, 2011).…”
Section: Introducción Objetivosunclassified
“…Widder, Senyi and colleagues (Widder et al, 1979;Senyei et al, 1978) reported the first preclinical experiments exploiting magnetic albumin microspheres loaded with doxorubicin in rats. However, the idea of taking advantage of iron oxide nanoparticles in biomedical and clinical ap-plications is not only because of their magnetic features but also thanks to their enormous potential in great number of biomedical and in vivo clinical applications, like magnetic resonance imaging (MRI) (Schlorf et al, 2011), magnetic hyperthermia treatment, tissue repair, contrast enhancement and gene (McBain et al, 2008) and/or drug delivery (Gupta et al, 2007;Viota et al, 2011).…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed the retention of the microspheres in the area of applied magnetic field by using an in vitro analog of the human circulatory system. [615] Since then, a lot of efforts were devoted in this area to improve MDT by designing various magnetic particles with minimized early clearance and more specific targeting to reduce the total dose required by increasing the concentration of drugs in blood vessels, especially in treating cancers. www.advancedsciencenews.com www.advhealthmat.…”
Section: Magnetic Drug Targetingmentioning
confidence: 99%
“…Therefore, an anionic group of the first surfactant is conjugated to the cation of the iron oxide on the inside, with the functional groups of the second surfactant compatible with the liquid base pointing towards the outside [4]. Because the magnetic nanoparticles have superparamagnetism characteristic [5,6], their fluid flow can be reversibly controlled and localized at a specific site in dependence on the external magnetic field strength [7]. The high temperature viscosity of the ferrofluids is significantly important for vacuum seals, because the temperature of the motor reaches ~57°C under normal operating conditions.…”
Section: Introductionmentioning
confidence: 99%